Understanding the Brazilian silvopastoral systems based on experimental data and functional-structural modeling - Vieira Junior, Nilson Aparecido (2021)
Currently, studies have shown the potential of silvopastoral systems to increase the sustainability of livestock production through the integration of trees, pastures, and animals. However, the addition of trees to the system can decrease pasture growth, make management and planning operations more complex, and thus limit its adoption. This study aimed to evaluate the incidence of solar radiation in silvopastoral systems and, based on experimental data and a functional-structural model, to evaluate different arrangements and management of trees in Brazil. For this, 50 photosynthetically active radiation points were glued between the tree rows, in addition to forage samples in 3 different treatments; 2 distances between rows of trees (4m and 15m) and full sun. It was found that the tree row orientation and the sun position throughout the year influenced the quality and production of forage. Forage production was lower closer to the tree row, with lower fiber content and higher production in all seasons in the center of rows. An approach was developed in which a functional-structural plant model was coupled to a process-based model for simulating the intercepted radiation by trees at different ages and forage production. Both models were calibrated with previously collected data. To simulate the different arrangements and managements in the systems, 29 agroclimatic zones were determined to represent the entire Brazilian livestock producing region. The simulated silvopastoral systems were selected by the combinations of spacing between rows (15, 30, and 45m), two orientations (North-South and East-West), and single or triple rows. The simulations were replicated for different tree ages (2, 4, 6, 8, 10, and 12 years). Tree management scenarios were simulated based on the most adopted practices by producers. For silvopastoral systems with simple rows, two managements were simulated: (i) pruning of 40% of the canopy and alternate thinning of 50% of the trees (M1) and (ii) pruning of 40% of the canopy of the trees (M2). For triple rows, the following managements were simulated: (i) pruning of 40% of the canopy and alternate thinning of 50% of the trees (M3) and (ii) pruning of 40% of the canopy of trees and thinning of external trees lines (M4). It was verified that all the silvopastoral systems arrangements showed satisfactory production in the first years of system implantation. Simulations for 2 year old trees indicated that forage biomass production levels ranged from 16,000 to 18,000 kg ha-1. The need for tree management practices was required 6 years after the implantation for arrangements with 15m spacing between rows. Pruning or thinning was recommended after 8 years for systems with a spacing of 30m and after 10 years for systems with a tree row spacing of 45m. This approach showed satisfactory results, being dan important tool to assist in planning and decision- making in these types of systems.